KECEMASAN MATEMATIKA PADA SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF: META-ANALISIS DAN STUDI EMPIRIS TENTANG MEKANISME KOGNITIF DAN EMOSIONAL - Intan Rofiah; Amin Sulistiyowati; Dian Kurniasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand mathematics anxiety in Children with Special Needs (ABK) in the context of inclusive schools, a topic that has not been widely researched so far. The study used a combined approach, combining a meta-analysis review from 14 reputable journals with an analysis of empirical data from 61 primary school students (7 ABK and 54 non-ABK). The aim was to analyze the relationship between math anxiety and teacher support. This research focuses on three specific mechanisms experienced by ABK: cognitive (related to working memory or memory), emotional (related to learning fear or trauma), and relational (related to teacher support). To ensure that the analysis was valid despite the limited number of ABK samples, the study used a special statistical technique called bootstrap resampling (with 1000 iterations). The main results were quite surprising and contrasting: In general, there was no significant difference in the level of math anxiety reported between ABK students (mean 2.09) and non-ABK students (mean 2.04). However, one critical behavioral difference was identified: ABK students significantly more often procrastinated on math assignments (p=0.025). Further analysis revealed that the main cognitive factor linking anxiety to achievement was working memory (memory to process information) (β = –0.13 to –0.27), not basic numeracy skills. This shows the existence of layered cognitive vulnerability in crew members, where the limitations of existing working memory are exacerbated by anxiety. Positively, students' perceptions of teacher support were found to be equal in both groups. This demonstrates equitable and non-discriminatory support practices in the school environment